Carnaval de Escada, Pernambuco, Brasil:: entre memórias e brincantes - Silva, Tarcisio Augusto Alves da; da Silva, Kaline Maria; Conserva, Rayanne Carolyne Lira (Latitude, 2023)
This article presents data from a research with records from newspapers and memories of revelers about the carnival in the city of Escada, Pernambuco (BR). The aim of the study is to systematically introduce these records and memories to understand the changes that the carnival in that city has been through. We also aim to introduce the main carnivalesque groups in the city as well as the most remarkable events in their history. The investigation relied on both primary (interviews) and secondary data (pictures, the group’s founding documents, newspapers, minutes and news websites) of the carnival in Escada. The results show the transformations, the disappearance and the revival of associations and events that constituted the carnival in the city.